Allogeneic hematopoietic stem cell transplantation in the COVID-19 era - Bordat, Jonathan; Maury, Sébastien; Leclerc, Mathieu (Frontiers in Immunology, 2023)
Allogeneic hematopoietic stem-cell transplantation (allo-HSCT) recipients are especially vulnerable to coronavirus disease 19 (COVID-19), because of their profound immunodeficiency. Indeed, the first pandemic wave was marked by a high mortality rate in this population. Factors increasing immunodepression such as older age, immunosuppressive treatments or a short delay between transplant and infection appear to worsen the prognosis. Many changes in clinical practice had to be implemented in order to limit this risk, including postponing of transplant for non-malignant diseases, preference for local rather than international donations and for peripheral blood as stem cell source, and the widespread use of cryopreservation. The great revolution in the COVID-19 pandemic came from the development of mRNA vaccines that have shown to be able to prevent severe forms of the disease. More than 75% of allo-HSCT recipients develop seroconversion after 2 doses of vaccine. Multiple studies have identified lymphopenia, exposure to immunosuppressive or anti-CD20 therapies, and a short post-transplant period as factors associated with a poor response to vaccination. The use of repeated injections of the vaccine, including a third dose, not only improves the seroconversion rate but also intensifies the immune response, both in B cells and T cells. Vaccines are an effective and well-tolerated method in this high-risk population. Some studies investigated the possibility of immune protection being transferred from a vaccinated donor to a recipient, with encouraging initial results. However, dynamic mutations and immune escape of the virus can lead to breakthrough infections with new variants in vaccinated individuals and still represent a threat of severe disease in allo-HSCT recipients. New challenges include the need to adapt vaccine protection to emerging variants.